On the commodity trail the journey of a bargain store product from East to West - Hulme, Alison; Taylor & Francis (Online service). (London NewYork Bloomsbury Academic, 2015)
"From raw materials on municipal rubbish dumps in the Far East, to newly re-made products and a journey across the seas, to bargain stores in Europe and North America and eventually to the homes of consumers, this is the complex story behind society's simplest and cheapest commodities. Weaving together compelling narratives from individuals at different parts of the commodity chain, including waste peddlers, wholesalers, stores owners and shoppers, this book considers the places and people at the heart of these localized, yet immense global networks. Following eight key objects, On the Commodity Trail combines ethnographies of material culture with a broader consideration of commodity culture at a time of global recession. This study explores the prevalence of the bargain store in our towns and cities and delves into the colourful and illuminating histories behind the objects on the shelf"-- Provided by publisher.
Machine generated contents note: -- PrefaceIntroduction: 8 Bargain Store Commodities and their Journeys 1. The Dump: Shanghai and Tianjin as Graveyards and Birthplaces of Commodities 2. The 'Commodity City': Yiwu, the World's Factory of Bargains 3. The Container Port: The Abundant Spaces of Felixstowe and Los Angeles 4. The Bargain Store: Buying and Selling in the West's Spaces of 'Cheap' Conclusion:... And Back to the Dump? Bibliography Index.
Includes bibliographical references (pages 143-150) and index.
Keywords: Electronic books; Discount houses (Retail trade); Variety stores; Consumer behavior; Consumption (Economics); Refuse collectors; Commercial products; BUSINESS & ECONOMICS / General; SOCIAL SCIENCE / Anthropology / General; SOCIAL SCIENCE / Sociology / General